Studying the antibiotics sensitivity test of Lactobacillus on two different media - Ban A. Abdul-sattar; Duaa S. Shawket; Afrah Mohammed Hassan Salman (College of Pharmacy / Mustansiriyah University, 2011)
The purpose of this paper is to study the antimicrobial susceptibility of twenty two different antimicrobial agents on three different isolates of Lactobacilli isolated from the vagina of healthy female by using disc diffusion method on Muller-Hinton agar and De Mann-Rogosa-Sharp (MRS) agar to determine the appropriate medium for susceptibility test and the pattern of resistant and sensitivity of Lactobacilli to different antimicrobial agents used for treatment of different infections. Lactobacilli were found resistant to Ceftazidime, Ciprofloxacin, Kanamycin, Nalidixic acid, Pipemidic acid, Streptomycin and Metronidazole, while they were sensitive to the rest of antibiotics used in this paper and this indicates that some antibiotics had effect on the presence of Lactobacilli (normal flora) inside the body.